An Insight of TiO2 and Spent Bleaching Earth (SBE) Effect of Phase Crystalline Structures for PVDF Hollow Fiber Membrane - Rhafiq Abdul Ghani; Muthia Elma; Aulia Rahma; Wahyu Wahyu (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Abstract: Polyvinylidene fluoride (PVDF) hollow fiber membranes have excellent mechanical properties and chemical stability. However, their hydrophobicity can lead to fouling and hinder permeability. Modifying this hydrophobicity is challenging due to PVDF's complex polymorphous structures, with the β-phase offering superior fouling resistance. One approach to improve PVDF hollow fiber membranes is the addition of inorganic additive materials to reduce hydrophobicity. The objective of this study is to offer new insights into the preparation of PVDF hollow fiber membranes using wet spinning with various additives, such as TiO2 and SBE. The investigation focused on the functional groups of PVDF in both the α and β phases. The membrane was fabricated using regenerated SBE and TiO2, which were incorporated through dope solution preparation and phase inversion through a wet spinning technique. The study used the Fourier Transform Infrared (FTIR) technique to characterize the PVDF hollow fiber membranes. The study found that the PVDF hollow fiber membranes exhibit differences in α and β phase crystalline structures when combined with various additives. The addition of SBE to PVDF hollow fiber membranes results in a dominant β-phase crystalline structure, as indicated by the relative fraction of 0.70 and the largest peak area of 2.27. This has successfully improved the hydrophilic properties of the PVDF-SBE hollow fiber membrane.Abstrak: Membran hollow fiber polyvinylidene fluoride (PVDF) memiliki sifat mekanik dan stabilitas kimia yang sangat baik. Namun, sifat hidrofobiknya dapat menyebabkan fouling dan menurunkan permeabilitas membran. Oleh karena itu memodifikasi sifat hidrofobisitas ini cukup menantang karena struktur polimorf PVDF yang kompleks, terutama dengan keberadaan fase β yang memberikan ketahanan terhadap fouling. Salah satu pendekatan yang dapat dilakukan untuk meningkatkan membran hollow fiber PVDF adalah dengan penambahan bahan aditif anorganik untuk mengurangi hidrofobisitas. Tujuan dari penelitian ini adalah untuk menguak wawasan baru dalam pembuatan membran serat berongga PVDF menggunakan wet spinning dengan berbagai aditif, seperti TiO2 dan SBE. Investigasi difokuskan pada gugus fungsional PVDF berupa fase α dan β. Membran dibuat dengan menggunakan TiO2 dan SBE regenerasi, yang dibuat melalui pembuatan larutan dope dan inversi fasa melalui metode wet spinning. Penelitian ini menggunakan teknik Fourier Transform Infrared (FTIR) untuk mengkarakterisasi membran serat berongga PVDF. Penelitian ini menemukan bahwa membran serat berongga PVDF menunjukkan perbedaan struktur kristal fase α dan β ketika dikombinasikan dengan berbagai aditif. Penambahan SBE pada membran serat berongga PVDF menghasilkan struktur kristal fase β yang dominan, seperti yang ditunjukkan oleh fraksi relatif 0,70 dan area puncak terbesar 2,27. Hal ini telah berhasil meningkatkan sifat hidrofilik membran serat berongga PVDF-SBE.